Antibiotic use and the risk of breast cancer: A systematic review and dose-response meta-analysis. (October 2020) - Simin, Johanna; Tamimi, Rulla M.; Engstrand, Lars; Callens, Steven; Brusselaers, Nele
Highlights: This is the first dose-response meta-analysis studying non-linear association. An increased risk of breast cancer was shown among antibiotic users. Penicillins, tetracyclines and nitrofurans showed the strongest increased risks. A protective effect of antibiotics was suggested after high cumulative use. This study highlights the need for more mechanistic studies. Abstract: Objective: Oral antibiotics are posed as a possible risk factor for breast cancer. Evidence is insufficient to determine whether the choice of antibiotic class could effect this potential association, and non-linearity has not been studied. We aimed to fill these important knowledge gaps. Methods: PubMed, Web of Science, Embase and a trial registry were searched from inception until January 2020, without any restrictions. Additionally, extensive manual searches were undertaken. Random-effects meta-analyses provided pooled risk estimates with 95 % confidence intervals (CI). Dose-response analyses modeling the relationship between number of antibiotic prescriptions and breast cancer risk were extended to non-linear models. Heterogeneity, publication bias and small-study effects were assessed. Results: Of 7805 identified publications ten were eligible, including 3, 719, 383 individuals and 84, 485 breast cancer cases. The pooled breast cancer risk was modestly increased among individuals who ever used antibiotics (relative risk RR = 1.18, 95 %CI 1.08–1.29), also after excluding the last year prior diagnosis. This excess risk was seen among penicillin (RR = 1.09, 95 %CI 1.01–1.18), tetracycline (RR = 1.13, 95 %CI 1.04–1.24) and nitrofuran users (RR = 1.26, 95 %CI 1.05–1.52), whilst nitroimidazole and metronidazole use (RR = 1.05, 95 %CI 1.00–1.11) indicated for marginal association. No apparent association was found for other antibiotics. Data suggested for a non-linear dose-dependent relationship, with a seemingly protective effect after at least 35 prescriptions. However, these findings might partly be explained by limited power of dose-response analyses. Conclusions: The association of antibiotics with breast cancer risk appears to differ between the various antibiotic classes. Whether this association is causal remains unclear, requiring further clarification and mechanistic studies.